Preparation of Ecofriendly Offset Printing Ink Varnish with Safflower Oil and Pinus pinaster Resin and Printability - (:unkn) unknown (My University, 2020)
Offset printing inks are composed of four main components including colorants, binders, solvents and additives. When these components are examined, it is seen that they contain petrochemical substances. During and after the printing process, some of these components are separated from the ink as waste material and are mixed with air, water or soil, thus damaging nature and human beings. Considering this problem, safflower oil and natural (Pinus pinaster) resin were used in this study to produce bio based offset printing ink varnish, one of the main components of the ink. Safflower oil and (Pinus pinaster) resin were mixed in different proportions to form varnish with suitable viscosity to the printing ink composition. The usability of these varnishes as an alternative for varnishes produced with mineral oil in standard offset printing ink was investigated. Magenta color standard offset printing ink was prepared with these varnishes and sample prints were printed on coated paper, uncoated paper, Bristol board with IGT C1 offset printability tester. Test prints were examined in terms of specialties such as drying, L*a*b and density with a spectrophotometer. As a result of the measurements and determinations, it was determined that the varnish produced with safflower oil and (Pinus pinaster) resin can be used instead of offset printing ink varnishes produced with mineral oil.

Ofset baskı mürekkepleri; renklendirici, bağlayıcı, çözücü ve katkı maddeleri olmak üzere dört ana bileşenden oluşmaktadır. Bu bileşenler incelendiğinde petrokimyasal maddeler içerdiği görülmektedir. Baskı sürecinde ve sonrasında bu bileşenlerin bazıları mürekkepten atık madde olarak ayrılarak havaya, suya veya toprağa karışmakta bu nedenle de doğaya ve insana zarar verebilmektedir. Bu problem göz önüne alındığında, mürekkebin ana bileşenlerinden biri olan biyo bazlı ofset baskı mürekkep verniği üretmek için aspir yağı ve doğal Pinus pinaster reçinesi kullanılmıştır. Aspir yağı ve sahil çamı reçinesi farklı oranlarda karıştırılarak baskı mürekkebi bileşimine uygun viskoziteye sahip vernik oluşturulmuştur. Elde edilen bu verniğin standart ofset baskı mürekkebinde mineral yağla üretilen vernikler yerine kullanılabilirliği incelenmiştir. Hazırlanan vernikle magenta renginde standart ofset baskı mürekkebi hazırlanarak IGT C1 ofset basılabilirlik test cihazı ile mat kuşe, 1. hamur kağıtlar ve Bristol karton üzerine numune baskılar yapılmıştır. Test baskıları üzerinde spektrofotometre ile inceleme ve ölçümler yapılarak verniğin; kuruma, densite ve L*a*b değeri gibi temel özelliklerine bakılmıştır. Ölçüm ve tespitlerin sonucunda aspir yağı ve sahil çamı reçinesi ile üretilen verniğin mineral yağla üretilen ofset baskı mürekkebi vernikleri yerine kullanılabileceği tespit edilmiştir.
Aspir Yağı ve Sahil Çamı Reçinesi ile Çevre Dostu Ofset Baskı Mürekkebi Hazırlanması ve Basılabilirliği